Centri-voltammetric detection of epinephrine. Issue 38 (7th September 2016) - Altuntas, Derya Bal; Ören, Tuğba; Anik, Ulku
Abstract : In this study, centri-voltammetry was applied to epinephrine detection for the first time. Abstract : The present study demonstrates a novel approach that has been proposed for epinephrine detection by using centri-voltammetry. The principle of the method is based on the accumulation of an analyte, here epinephrine, onto an electrode surface via centrifugal force. After the accumulation of epinephrine, a direct voltammetric scan was performed in a specially fabricated centri-voltammetric cell. A remarkable increase in the oxidation peak current of epinephrine was observed in the case of centrifuge application. Experimental parameters like the centrifugation speed and centrifugation time were optimized and then the analytical characteristics were examined. Two linear ranges were obtained between 0.2–20 μM and 50–500 μM for epinephrine and limit of detection (LOD) values were also calculated for both linear ranges to be 0.013 μM and 0.043 μM, respectively. As a practical application, the developed method was applied to epinephrine detection in adrenaline ampoule samples.